CONTRIBUTION OF SUFISTIC PSYCHOTERAPY TO THE MENTAL HEALTH OF THE ELDERLY - M. Agus Wahyudi; Salami Salmi; Warul Walidin (VIRTUOUS JOURNAL, 2024)
Sufistic psychotherapy is part of the development of Islamic psychotherapy. Namely psychotherapy based on sufistic values. Sufism (sufistic) is a science that aims to cleanse the human soul to draw closer to God. So that it has a relationship with the mental or mental condition of a Sufism practitioner. Mental health is the condition of an individual who realizes the potential in himself, the ability to overcome problems in his life, is able to develop, is productive and has psychological well-being. The elderly are one of the individuals who are vulnerable to experiencing mental health disorders. So, through sufistic psychotherapy it is hoped that it can help improve the mental health experienced by the elderly. This research uses a qualitative approach with a literature study method. The purpose of this study is to find out what sufistic psychotherapy is, and how sufistic psychotherapy contributes to the mental health of the elderly. The results of this study, that thought, salat, and puasa carried out sufistically (full of passion) can overcome mental health problems experienced by the elderly, such as depression, anxiety, and post power syndrome.